Вплив фізико-хімічних параметрів компонентів поверхнево-активних систем на мінімізування випаровування вуглеводневих рідин - Spas'ka, O.A.; Chumak, V.L.; Maksymyuk, M.R.; Rudenko, V.M.; Kosenko, O.I.; Polunkin, E.V.; Gaidai, O.O. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2021)
Highly efficient stable aerated hydrophilic compositions containing fluorotensides and ultralight microdisperse systems using gas-filled glass, aluminosilicate and polymer microspheres have been developed. Designing the compositions of PAS based on the surface activity of surfactants, their solubility in water and the ability to bind water and the formation of hydrogen bonds between the components. The main condition for the stability of the coating when mixing the components - the chemical interaction between them and the formation of a system that does not dissolve in hydrocarbons and does not break down in terms of use. The best film-forming characteristics necessary for the operation of the coating (simultaneous reduction of surface tension and film formation) active substances (FPAR), the non-polar part of the molecules of which contains a fluorocarbon chain, so they are insoluble in hydrocarbons, well soluble in water and easily distributed on the surface of hydrocarbon liquids, creating a protective film. The choice of co-surfactants was based on the ability to stabilize hydrophilic films on the surface of hydrocarbons not only at favorable HLB, but also at the lowest, although higher than the critical concentration of micelle formation (CCM), concentrations for forming a mixed adsorption layer of increased strength. This surfactant was water-oil-soluble twin80, which will significantly increase the hydrophilic part and enhance the stability of the PAS and the stability of the aerated system. The introduction of glass microspheres into the components of the system has significantly enhanced its strength and stability. In the study of the stability and gas permeability of the developed surfactant systems, it was found that the insulating ability of the coating increases with increasing hydrophilic-lipophilic balance of the system and due to chemical interaction between the carboxyl group of fluorotenside and hydroxyl groups of surfactants.